The Effect of Quetiapine versus Haloperidol on Delirium Severity in Hospitalized adults; A Systematic Review and Meta Analysis - Shiza Zainab, Nawal Zahra (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Delirium is a neuropsychiatric disorder associated with many adverse outcomes. Although both quetiapine and haloperidol have been individually studied for delirium management, there is a lack of direct comparison between the two. We addressed this gap in our analysis. Objectives: To compare the effects of quetiapine and haloperidol on delirium severity, response rates, mortality, hospital and ICU length of stay (LOS), and adverse events in hospitalized adults. Methods: In accordance with PRISMA guidelines, we conducted a systematic search of PubMed, Cochrane, Embase, and Google Scholar. Three RCTs with 215 patients met the inclusion criteria after review of 60 relevant articles. Delirium severity was compared as the primary outcome, and mortality, adverse events, and length of stay as secondary outcomes. Data analysis was conducted using the Random-effects model in Review Manager (RevMan 5.4.1). This review is registered with PROSPERO (CRD420251040521). Results: There were no statistically significant differences in mortality (Risk Ratio: 0.60, 95% CI: [0.29, 1.27], P = 0.18), sleep time (Mean Difference: 1.59, 95% CI: [-0.45, 3.63], P = 0.13) and response rate (Risk Ratio: 0.89, 95% CI: [0.51, 1.56], P = 0.69) between the two groups due to high heterogeneity. Furthermore, for delirium severity (Mean Difference: -0.80, 95% CI: [-2.05, 0.44], P = 0.21) and cognitive function (Standardized Mean Difference: -0.09, 95% CI: [-0.45, 0.28], P = 0.65), the heterogeneity was low, but the results remained statistically insignificant. Conclusion: While both quetiapine and haloperidol offer distinct benefits, there is a need for additional, comprehensive and high-quality RCTs to determine optimal pharmacological interventions for delirium management. Conflict of Interest and Funding: We declare no conflict of interest. No funding was received. Keywords: Quetiapine, Haloperidol, Delirium